The naturalistic turn in economics: implications for the theory of finance - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2008)
Economics is increasingly adopting the methodological standards and procedures of the natural sciences. The paper analyzes this 'naturalistic turn' from the philosophical perspective on naturalism, and I discuss the implications for the field of finance. The theory of finance is an interesting case in point for the methodological issues, as it manifests a paradigmatic tension between the pure theory of finance and Behavioral Finance. I distinguish between three kinds of naturalism: mark I, the reduction of behavior on psychoneural phenomena, mark II, the transfer of patterns of causal explanations from the natural sciences to the social sciences, mark III, the enrichment of the ontology from observer-independent to observer-relative facts. Building an integrated naturalistic paradigm from these three ingredients, I show that naturalism in economics will only be completed by a simultaneous linguistic turn, with language being analyzed from the naturalistic viewpoint. I relate this proposition with recent results of research into finance, especially connecting Behavioral Finance with the sociology of finance.
urn:nbn:de:101:1-2008121076
Keywords: A12; B41; D87; G00; 330; Naturalism; causation in economics; neuroeconomics; behavioral finance; social ontology; sociology of finance